Some characteristics about the context. (Journal of Parents and Teachers, 2014)
There are ten aspects to build the Scholar Curricular Project like the concept teaching-learning, teacher’s training, new ways to organize schools, competences and more elements related to that project.
Keywords: education; context; project; curriculum; school; competence; organization.